Genome-wide identification of the Sec14 gene family and the response to salt and drought stress in soybean (Glycine max) - Jinyu Zhang; Liying Zou; Li Wang; Dongchao Zhang; Ao Shen; Yongqi Lei; Maoni Chao; Xinjuan Xu; Zhiwei Xue; Zhongwen Huang (BMC Genomics)
Abstract Background The Sec14 domain is an ancient lipid-binding domain that evolved from yeast Sec14p and performs complex lipid-mediated regulatory functions in subcellular organelles and intracellular traffic. The Sec14 family is characterized by a highly conserved Sec14 domain, and is ubiquitously expressed in all eukaryotic cells and has diverse functions. However, the number and characteristics of Sec14 homologous genes in soybean, as well as their potential roles, remain understudied. Results In this study, we identified 77 Sec14 genes in the soybean genome that were unevenly distributed across 19 chromosomes. Based on the classification method used for Arabidopsis Sec14 members, GmSec14s can be categorized into three classes: GmPITP1 to GmPITP37, GmSFH1 to GmSFH25, and GmPATL1 to GmPATL15. Structural analysis of the GmSec14 genes revealed that the SFH subfamily contained more introns than the other subfamilies. A total of 10 conserved protein motifs were detected within GmSec14 proteins, with each subfamily possessing unique motifs. Two tandem duplications and 73 segmental duplications were identified among the GmSec14 genes. Additionally, a large number of cis-acting elements, particularly those related to plant hormones, were abundant in the promoter regions of the GmSec14 genes. Tissue expression analysis of the GmSec14 genes indicated that they exhibited distinct tissue-specific expression patterns. In response to salt stress, multiple genes were found to be either upregulated or downregulated. In contrast, the majority of genes were downregulated under drought stress conditions. Notably, 12 GmSec14 genes exhibited significant alterations in expression following salt or drought stress, suggesting a potential role for these genes in stress response mechanisms. Furthermore, the protein interaction network and miRNA regulation associated with GmSec14s were predicted to elucidate the potential functions of GmSec14 members. Conclusions This study provides a systematic and comprehensive examination of the Sec14 gene family in soybean, which will facilitate further functional research into their roles in response to salt and drought tolerance.